Entrepreneurship and the Relation with Mission in the Church of Indonesia - Dekker, Peter (Sekolah Tinggi Theologia Jaffray, 2020)
How important is Entrepreneurship in the context of the church of Indonesia? A sketch of the common situation and a desirable situation. How can the church grow when there is still a paradox about the relation between: “Entrepreneurship and the church”? What could be the future for the church in a rapidly changing Indonesia? In this article, the author wants to describe the current status of the church in Indonesia. The author also wants to discuss the rise of Islam in Indonesia. Finally, the author wants to develop a model that will help Christians gain recognition in areas that not have been reached with the gospel in Indonesia today. The author will do this on the basis of his experiences in recent years when working in Indonesia to establish bridges between Christians and Muslims in an area that has not yet been reached. The author did this by setting up and starting up activities that give Christians a legitimate status in that area. From this legitimate status arise relationships and contacts with the local population. The focus of this article is on his experiences. The church is experiencing major difficulties in Indonesia in and after 2020. How can the church in Indonesia go out and reach people who do not yet know Jesus as their Savior and Lord?